Diagnostic and therapeutic strategies for vascular complications after renal transplantation: a single-center experience in 2,304 renal transplantations - Zhang, Jiangwei; Xue, Wujun; Tian, Puxun; Zheng, Jin; Ding, Chenguang; Li, Yang; Wang, Ying; Ding, Xiaoming (Frontiers in Transplantation, 2023)
Vascular complications after renal transplantation are one of the serious surgical complications, which can affect the transplantation outcome and even endanger life if not treated properly. We performed a retrospective analysis 2304 renal transplant procedures completed between the period of 01.2015 and 01.2022, which consisted of 1658 male patients and 646 female patients, there were 57 cases of vascular complications after renal transplantation, the incidence of vascular complications in our study was 2.47% (57/2304), the most common vascular complication was transplant renal artery stenosis (TRAS, n=36), followed by external iliac artery dissection (n=5), renal artery rupture (n=4), renal vein thrombosis (n=3), renal rupture (n=3), renal artery thrombosis (n=2), renal artery dissection (n=1), renal artery pseudoaneurysm (n=1), and internal iliac artery pseudoaneurysm (n=1). 40 patients were treated by percutaneous transluminal angioplasty (PTA), including 3 balloon catheter dilatation and 37 endovascular stentings, and 17 underwent open surgery. Eventually, 11 patients (19.3%) had their transplanted renals removed, resulting in an overall treatment rate of 70.2%. Most vascular complications can be treated satisfactorily with PTA. However, the overall treatment of renal artery rupture, thrombosis, renal artery kinking, and other complications is poor, and the rate of transplanted renal loss is high.